Prevalence of symptomatic dry eye and influencing factors among Chinese adolescents: A cross-sectional study - Chen, Xiaojuan; Zhou, Yue; Gao, Xian; Zhu, Yan; Cai, Qi; Yin, Bianyu; Sun, ZhiMin; Xiong, Yaojia; Wang, Yong; Huang, Xiaobo (PLOS ONE, 2024)
Background Comprehensive research on the impact of various types of refractive errors (RE) and anisometropia on dry eye disease is still lacking. This study aimed to estimate the prevalence rates and potential lifestyle factors related to symptomatic dry eye (SDE) among adolescents in eastern China. Methods A cross-sectional study was performed in 2023, and a stratified cluster sampling technique was used among adolescents in Nantong, China. Demographic information, including sex, age and BMI, were collected. All participants underwent optometric tests, while Ocular Surface Disease Index (OSDI) and self-designed questionnaires were administered. Both univariate and multivariate logistic regression analyses were used to assess associations between SDE and related parameters, and various types of RE and anisometropia were also included in the study. Results A total of 1,518 participants were enrolled in the study, and the overall prevalence of SDE was 20.3% among adolescents in Nantong, China. Multiple logistic regression analyses showed that high myopia (aOR = 3.42, 95% CI = 1.60–3.36, p = 0.025), frequent use of eye drops (aOR = 2.31, 95% CI = 1.60–3.36, p<0.001), a history of allergic conjunctivitis (aOR = 1.93, 95% CI = 1.09–3.34, p = 0.025), and frequent blinking (aOR = 3.23, 95% CI = 2.31–4.53, p<0.001) were identified as risk factors for SDE. Conversely, male gender (aOR: 0.76, 95% CI: 0.58–0.99, p = 0.043), increased sleep time (6–7 h: aOR = 0.64, 95% CI = 0.46–0.89, p = 0.009; 7–8 h: aOR = 0.64, 95% CI = 0.43–0.95, p = 0.026; >8 h: aOR = 0.43, 95% CI = 0.23–0.82, p = 0.010), and timely intervention when vision decline occurred were protective factors against SDE (aOR = 0.61, 95% CI = 0.43–0.85, p = 0.004). Conclusion High myopia was found to be independently associated with an increased risk of SDE., while hyperopia, astigmatism, and anisometropia were not independent risk factors for SDE. The identified risk and protective factors may help provide valuable insights for future research and interventions aimed at improving ocular health in adolescents.